University Students: Between the Digital Divide and Learning in Times of COVID-19. The Case of the National University of Costa Rica (UNA), Chorotega Region Campus, Liberia, Costa Rica - Chanto Espinoza, Carlos (2020)
This research examines the practices of university students for whom the training process has been modified due to COVID-19 pandemics; the process adopted a remote attendance of courses that interacts with virtual learning spaces. Because of the challenges posed, a study was implemented whose objective was to analyze the effects of access to ICTs by university students from the National University (UNA), Chorotega Region Campus, Liberia, Costa Rica, and its possible repercussions on teaching-learning processes. This was achieved by conducting a study with a quantitative, descriptive, and explanatory approach; the study was conducted in a sample of 221 university students. The results revealed wide inequalities in the following four components in different student groups: connectivity, technological resources, inconveniences, and alternate complications. Besides, the results showed that, in the interaction with ICTs, there is an evident discrepancy in access to digital resources, known as the digital divide. Important variables to be considered to address the mental health of students and teachers also stand out. The research establishes that digital literacy is a social challenge still pending. Therefore, recommendations are proposed to the UNA’s different instances, especially to the Office of the Vice President for Student Welfare and the Office of the Vice President for Teaching.